An Overview of Lifestyle in Communities During The Second Wave of Covid-19 Pandemic - Eppy Setiyowati; Umi Hanik; Nunik Purwanti (Universitas Nahdlatul Ulama Surabaya, 2021)
Coronavirus 2019 (COVID-19) is a virus causing high mortality rates in variouscountries. So, the communities make preventive efforts with healthy lifestyle behaviors.The research aims to study lifestyle behaviors and community health conditions during the Covid 19 pandemic. This paper was a quantitative research design with a cross-sectional approach. In addition, the population was 170 respondents domiciled in Surabaya. Sampling techniques used simple random sampling. Data collection throughthe dissemination of questionnaires in google form circulated through WhatsApp group.Furthermore, the data were analyzed with a Linear Regression Test with  = 0.005. Theanalysis results gained public knowledge about the COVID-19 pandemic in the Lowcategory (13.94%). In addition, in public behavior variable showed that the communitydid not comply with health protocols during the COVID-19 pandemic (59.18%). Mostrespondents were in the category of low-risk cases. Linear statistic regression test resultsshowed lifestyle related to knowledge, healthy behavior, obedient protocol Health andhealth condition in individuals (= 0007). Public Health Condition is an indicator of thesuccessful assessment of the disconnection of the covid 19 spread chain. Future researchshould analyze awareness, compliance, and the willingness of the community to carryout health protocols.